Factors Affecting the Waiting Time of Pedestrians at Unsignalized Crosswalks of Kathmandu: A Case Study of Bagbazar and Jamal Crosswalks - Thapaliya, Sudeep; Pradhananga, Rojee; Shrestha, Saurav (International Journal on Engineering Technology, 2024)
Unsignalized crosswalks are the most common pedestrian crossing facilities on the city roads of Kathmandu. This sharing of the road between pedestrians and vehicles can be very unsafe for walking. To demur such conflict, analyzing pedestrians' waiting behavior and designing pedestrian signals considering different factors is the most efficient way. The degree to which pedestrians adhere to signals depends largely on their patience while waiting. Thus, it is crucial to account for pedestrian waiting tolerance when planning pedestrian signal timing. A study at unsignalized crosswalks of Bagbazar and Jamal were taken into consideration for this study. This research delves into analyzing the factors that impact the waiting time, a key indicator of pedestrian patience at unsignalized crosswalks in Kathmandu. Using SPSS, binary logistic regression is conducted with the waiting time of a pedestrian before crossing as the dependent variable and road width, the gap between vehicles, speed of accepted vehicles, pedestrian size, gender, crossing pattern, and the presence of a carried object as predictor variables. The article encountered that gender, crossing pattern, carrying any object, size of pedestrians, road width, and time gap between the vehicles at the nearer lane of a pedestrian are the significant factors that affect the waiting time. The results could be employed by planners to coordinate the design of pedestrian crossing facilities with the behavioral patterns of pedestrians at unsignalized crosswalks.